Enhancing the adsorption behavior and mechanism of Sr(ii) by functionalized montmorillonite with different 3-aminopropyltriethoxysilane (APTES) ratios. Issue 86 (2nd September 2016) - Liu, Chongmin; Liu, Shuai; Wu, Pingxiao; Dai, Yaping; Tran, Lytuong; Zhu, Nengwu; Guo, Chuling; Sohoo, Ihsanullah
Abstract : APTES functionalized montmorillonite has potential applications in the removal of Sr(ii ) from wastewater by coordination–adsorption. Abstract : Modified calcium saturated montmorillonite (Mt) was prepared at different 3-aminopropyltriethoxysilane (APTES) loadings through grafting. The as-products were characterized by XRD, FTIR and elemental analysis. Surface analysis such as acidity was examined at different H + concentrations, showing that the release of OH − from the modified samples increased in the following order: APTES4.0CEC –Mt > APTES3.0CEC –Mt > APTES2.0CEC –Mt > APTES1.0CEC –Mt. Batch experiments were conducted and different conditions (pH, temperature and co-existing ions) were used to evaluate the adsorption capacity of the modified samples. The study developed a new way to confirm the mechanism, which indicated that ligand adsorption was the dominant sorption mechanism for Sr(ii ) uptake onto APTES–Mts. In general, APTES grafted montmorillonite possessed a higher efficiency of Sr(ii ) uptake and showed great potential for Sr(ii )-rich wastewater treatment.